Efektivitas Penyelenggaraan Tempat Pelelangan Ikan (TPI) Desa Sungaibuntu Kecamatan Pedes Kabupaten Karawang Jawa Barat - Febryanto , Fadli; Sam’un , Mohamad; Azzahra , Fatimah (Paspalum: Jurnal Ilmiah Pertanian, 2024)
The fish auction serves as a marketing center for the distribution of fish. The implementation of the fish auction is expected to enhance the selling prices of the fishermen's catch. The purpose of this research is to analyze the level of effectiveness of the fish auction implementation. Effectiveness is measured in two ways: first, effectiveness is measured using the Mahmudi formula. Variables measured include the number of boats landing fish at the fish auction, fish production, fish prices, revenue, auction fees, fish auction operational activities, and the reporting system at Sungaibuntu’s fish auction. Second, effectiveness is measured according to the fishermen's perceptions, with variables including fish auction as a facility, auction activities, and services. This research also analyzes the comparison of fish prices and the income of fishermen selling fish at the fish auction and outside the fish auction. This research uses descriptive quantitative methods. Primary data collection involves field observations, questionnaires, and interviews, while secondary data is obtained from relevant institutions, theses, and journals. Simple random sampling is used to obtain 37 fishermen respondents. The research results show that the overall effectiveness ratio values measured by the Mahmudi’s formula for the period 2020-2022, for the effectiveness of boat activities, auction fees, fish production, and auction revenue, are categorized as "Less Effective." Meanwhile, the effectiveness of TPI operational activities and monitoring reporting systems achieves a level of "Very Effective," and the effectiveness of fish prices at Sungaibuntu TPI reaches the level of "Effective." For effectiveness measured according to the fishermen's perceptions, the variables of fish auction as a service and facility are categorized as "Less Effective." Meanwhile, fish auction as a facility is categorized as "Effective." There is a difference in the income of fishermen selling fish at the fish auction compared to fishermen selling fish outside the fish auction.